Herr Lubitsch Goes to Hollywood German and American Film after World War I - Thompson, Kristin (Film Culture in Transition, 2005)
Ernst Lubitsch, the German film director who left Berlin for Hollywood in 1923, is best remembered for the famous "Lubitsch touch" in such masterpieces as Trouble in Paradise and Ninotchka, featuring Greta Garbo. Kristin Thompson's study focuses on Lubitsch's silent films from the years between 1918 and 1927, tracing the impact this director had on consolidating classical Hollywood filmmaking. She gives a new assessment of the stylistic two-way traffic between the American and the German film industries, after World War I each other's strongest rival in Europe. By 1919, Lubitsch had emerged as the finest proponent of the German studio style: sophisticated, urbane and thoroughly professionalized. He was quick to absorb 'American' innovations and stylistic traits, becoming the unique master of both systems and contributing to the golden ages of the American as well as the German cinema. Utilizing Lubitsch's silent films as a key to two great national cinemas, Thompson's meticulously illustrated and extensively researched book goes beyond an authorial study and breaks new ground in cinema history. Click on the PDF button to download the table of contents